Sources of Nitrate in Ground Water Aquifers of the Semiarid Region of Tanzania. (22nd June 2021) - Alex, Rita; Kitalika, Aldo; Mogusu, Emmanuel; Njau, Karoli
Abstract : Nitrate isotopic values are often used as a tool to identify sources of nitrate in order to effectively manage ground water quality. In this study, the concentrations of NO3 −, NO2 −, and NH4 + from 50 boreholes and shallow wells in the Singida and Manyoni Districts were analyzed during the dry and wet seasons, followed by identification of nitrate sources using the hydrochemical method (NO3 − /Cl − ) and stable isotope ( δ 15 N and δ 18 O) techniques. Results showed that NO2 − and NH4 + concentrations were very low in both seasons due to the nitrification process. The concentrations of NO3 − ranged from 2.4 ppm to 929.6 ppm with mean values of 118.5   ppm ± 118.5   ppm, during the dry season and from 2.4 ppm to 1620.0 ppm with mean values of 171.6   ppm ± 312.3   ppm, during the wet season. The higher NO3 − contamination observed in the wet season could be due to rainfall which accelerated the surface runoff that collects different materials from various settings into the ground water sources. Nitrate source identification through hydrochemical technique revealed that most nitrates originated from sewage effluents and/or organic wastes such as manure. Likewise, the mean values of δ 15 N-NO3 − (+ 20.90 ‰ ± 5.17 ‰ and + 18.30 ‰ ± 6.33 ‰ ) and the mean values of δ 18 O-NO3 − (+ 13.86 ‰ ± 3.18 ‰ and + 13.69 ‰ ± 3.97 ‰ ) suggest that 80% of boreholes and 52% of shallow wells were dominated with nitrate from sewage effluents and/or manure as most ground water sources were situated in densely populated areas with congested and poorly constructed onsite sanitation facilities such as pit latrines and manure. Therefore, to reduce nitrate pollution in the study area, a central sewer must be constructed to treat the discharged wastes. Also, groundwater harvesting should consider the proper principles for groundwater harvesting recommended by the respective authority to minimize chances of contamination and hence prevention of health risk.